Smart Indonesia Program Implementation Evaluates Educational Resource Organization And Policy Interpretation: Implementasi Program Indonesia Pintar Mengevaluasi Organisasi Sumber Daya Pendidikan Dan Interpretasi Kebijakan - Ais Arfia Febrianti; Ilmi Usrotin Choiriyah; Dita Dwi Lestari; Ella Tinara; Risa Salsabila Fransisca; Rima Widya Sari (Proceedings of The ICECRS, 2025)
General Background Education serves as a central foundation for national advancement by empowering individuals to develop essential knowledge and skills. Specific Background Economic disparities present a major challenge to educational equity in Indonesia, prompting the government to launch the Smart Indonesia Program to provide financial assistance to students from low-income families. Knowledge Gap Although administrative structures and technical disbursement channels are operational, practical implementation encounters challenges regarding suboptimal policy socialization to parents and a lack of systematic fund utilization monitoring by schools. Aims This descriptive qualitative case study analyzes the implementation of the Smart Indonesia Program at SMK Negeri 1 Buduran. Results Findings demonstrate that resource organization and technical disbursement mechanisms function successfully through established organizational structures and digital verification workflows, yet policy socialization remains suboptimal and school-level fund monitoring is absent. Novelty This research specifically identifies the operational friction between automated digital website verification and the persistent lack of direct stakeholder socialization and fund utilization supervision. Implications Educational institutions must intensify outreach efforts and establish robust monitoring systems to ensure that aid funds are appropriately utilized for student educational needs. Highlights: Resource organization exhibits structured administrative frameworks, competent personnel, and adequate technological facilities for aid distribution. Policy socialization to parents and guardians remains suboptimal due to institutional assumptions regarding prior student program familiarity. The absence of school-level fund monitoring creates uncertainties regarding the allocation of financial assistance for educational purposes. Keywords: Smart Indonesia Program, Policy Implementation, Resource Organization, Policy Interpretation, Educational Assistance